Ministry Of Trade And Industry Decree No. 912 Of The Year 2017 Imposing Energy Consumption Labels To Be Fixed On Appliances, Electric Lamps And Lighting Units in Whose Respect the Egyptian Standard Specifications on Energy Efficiency Labels are Issued = وزارة التجارة والصناعة قرار رقم 912 لسنة 2017 بشأن الإلزام بوضع بطاقات استهلاك الطاقة على الأجهزة والمصابيح الكهربائية ووحدات الإضاءة الصادر بشأنها مواصفات قياسية مصرية لبطاقة كفاءة الطاقة - The Middle East Library for Economic Services (The Middle East Library for Economic Services, 2025)
English & Arabic